Umbilical true knot: a case study - Kommuri, Hima Bindu; Diana G., Valsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Umbilical cord true knot is a rare condition which affects about 1% of all pregnancies. The incidence is not only very low, but it is often undiagnosed antenatally when present despite the availability of prenatal ultrasonography as in this case, where the diagnosis of true knot of umbilical cord was missed even when an ultrasonogram was done 1 week prior to the presentation of patient with decreased fetal movements to opd. Majority of times it does not have any relation with fetal outcome but in certain occasions it is associated with intrauterine fetal demise as in present case presented here. Risk factors include long umbilical cord, polyhydramnios, small fetus, male fetus, etc.